Circularly Polarized Dipole Antenna fed by Dual Quadrature Hybrid Couplers - Wang, Heesu; Park, Ikmo (2021 IEEE International Symposium on Antennas and Propagation and North American Radio Science Meeting, APS/URSI 2021 - Proceedings, 2021)
A circularly polarized (CP) dipole antenna fed by dual quadrature hybrid couplers (QHCs) is presented in this paper. In a conventional CP antenna, such as a sequentially rotated structure, the electrical length of the line connecting the radiating elements changes as the frequency changes. A modified QHC with minimal variation in the phase and amplitude difference between the output ports over a wide frequency range is used to achieve wide AR bandwidth and stable radiation patterns. The antenna with a compact dimensions of 0.42_o× 0.42_o× 0.004_o at 6 GHz. has -10 dB impedance bandwidth of 4.3-7.6 GHz, the 3-dB AR bandwidth of 4.9-7.9 GHz, and the 3-dB gain bandwidth of 5.0-7.5 GHz.
Keywords: Amplitude difference; Antenna feeds; Circularly polarized antennas; Circularly-polarized; Electrical length; Frequency changes; Phase difference; Quadrature hybrid couplers; Radiating elements; Wideband antenna; circularly polarized antenna; dipole antenna; quadrature hybrid coupler; wideband antenna